Dampak Profitabilitas, Leverage, Ukuran Perusahaan dan Intensitas Aset Tetap Terhadap Penghindaran Pajak Pada Masa Pandemi Covid-19 - Evangelica, T, Gracella Christhalia; Subagio, Indra Sukma (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research aims to determine the impact of profitability, leverage, firm size, intensity of fixed assets on tax avoidance. The population in this study are all manufacturing companies in Indonesia that are listed on the Indonesia Stock Exchange for the 2020-2022 period. The selection of the sample in this study used a purposive sampling method and obtained a sample of 79 samples. Source of data used is secondary data. Based on multiple linear regression analysis using the SPSS 26 program, it is found that tax avoidance is not affected by profitability, leverage, firm size, intensity of fixed assets.